R package - HultenRangeMaps - Arnell, Matilda (Stockholm University, 2026)
This dataset contains an R package (R Core Team 2025) with the methods employed to digitise the historical range maps in the ‘Atlas of the distribution of vascular plants in northwestern Europe’ (Hultén 1971). Methods include georeferencing the scanned maps, extract range data, clean data and convert data from raster to spatial polygon data. A detailed description of how the original atlas was compiled as well as the method used to georeference and digitize the distribution maps can be found in Arnell et al. (2026a). The resulting dataset can be found at https://doi.org/10.58141/y1x5-cx68 (Arnell et al. 2026b).
A package tutorial with examples can be found at GitHub https://github.com/ArnellM/HultenRangeMaps/.
The package contains two functions to extract and clean distribution data from the scanned maps, one function to modify file names and one function to match the distribution data to polygon grids commonly used when analysing historical atlas data.
Installation
This package can be installed using devtools (Wickham et al. 2025). To insure reproducibility, we have created a ‘mini’ repository with all the packages that the functions in HultenRangeMaps require. The repository is included in the documentation files (HultenRangeMaps_miniCRAN_June2025.zip) and at GitHub https://github.com/ArnellM/HultenRangeMaps_miniCRAN_June2025. First, download the repository to your computer. Then, decompress the folder and install the packages from your local repository using the code below.
# list of packages that the functions in HultenRangeMaps require
pkgs <- c("dplyr", "gtools", "raster", "sf", "terra", "tidyr")
# path to where you have downloaded the local miniCran repository
pth <- "/HultenRangeMaps_miniCRAN_June2025"
# install packages from your local miniCRAN repository
install.packages(pkgs, repos = paste0("file:///", pth), type = "source")
# install HultenRange maps
install.packages(c("devtools", "rtools"))
library(devtools)
install_github("ArnellM/HultenRangeMaps")
library(HultenRangeMaps)
References
Arnell, M., Auffret, A. G., & Hylander, K. (2026a). Historical distribution maps of vascular plants in Northern Europe. (Accepted for publication in Ecology).
Arnell, M., Auffret, A. G., & Hylander, K. (2026b). Historical distribution maps of vascular plants in Northern Europe (Version 1) [Data set]. Stockholm University. https://doi.org/10.58141/y1x5-cx68
Hultén E. (1971). Atlas of the distribution of vascular plants in northwestern Europe (2nd ed.). Generalstabens Litografiska Anstalts Förlag.
R Core Team. (2025). R: A language and environment for statistical computing [Computer software]. R Foundation for Statistical Computing. https://www.R-project.org/
Wickham H., Hester J., Chang W., Bryan J. (2025). devtools: Tools to Make Developing R Packages Easier. R package version 2.4.6, https://devtools.r-lib.org/.

Detta dataset innehåller ett R-paket (R Core Team 2025) med de metoder som använts för att digitalisera de historiska utbredningskartorna i "Atlas över växternas utbredning i norden" (Hultén 1971). Metoderna inkluderar georeferering av de skannade kartorna, extrahering av utbredningdata, automatiserad redigering av datat och konvertering av datat från raster till polygoner. En detaljerad beskrivning av hur den ursprungliga atlasen sammanställdes samt metoden som användes för att georeferera och digitalisera utbredningskartorna finns i Arnell et al. (2026a). Databasen med de digitaliserade utbradningskartorna finns här https://doi.org/10.58141/y1x5-cx68 (Arnell et al. 2026b).
En beskrivning av R-paketet med exempel finns på GitHub https://github.com/ArnellM/HultenRangeMaps/.
Paketet innefattar två funktioner för att extrahera och redigera distributionsdata från de skannade kartorna, en funktion för att ändra filnamn och en funktion för att matcha distributionsdata med valfritt rutnät (till exempel Rikets nät 10×10 km) som vanligtvis används vid analys av historiska atlasdata.
Installation
R-paketet "HultenRangeMaps" kan installeras med hjälp av devtools (Wickham et al. 2025). För att säkerställa att paketet kommer att fungera även om de paket som våra funktioner bygger på uppdateras har vi skapat ett "mini"-arkiv med alla paket som funktionerna i HultenRangeMaps kräver. Arkivet ingår i dokumentationsfilerna (HultenRangeMaps_miniCRAN_June2025.zip) och på GitHub https://github.com/ArnellM/HultenRangeMaps_miniCRAN_June2025. Ladda först ner arkivet till din dator. Packa sedan upp mappen och installera paketen från ditt lokala arkiv med hjälp av koden nedan.
# lista över paket som funktionerna i HultenRangeMaps är beroende av
pkgs <- c("dplyr", "gtools", "raster", "sf", "terra", "tidyr")
# sökväg till mappen där du har laddat ner det lokala miniCran-arkivet
pth <- "/HultenRangeMaps_miniCRAN_June2025"
# installera paket från ditt lokala miniCRAN-arkiv
install.packages(pkgs, repos = paste0("file:///", pth), type = "source")
# installera HultenRange-kartor
install.packages(c("devtools", "rtools"))
library(devtools)
install_github("ArnellM/HultenRangeMaps")
library(HultenRangeMaps)
Referenser
Arnell, M., Auffret, A. G., & Hylander, K. (2026a). Historiska utbredningskartor för kärlväxter i norra Europa. (Accepterad för publicering i Ecology).
Arnell, M., Auffret, A. G., & Hylander, K. (2026b). Historiska utbredningskartor för kärlväxter i norra Europa (Version 1) [Datamängd]. Stockholms universitet. https://doi.org/10.58141/y1x5-cx68
Hultén E. (1971). Atlas över växternas utbredning i norden (2a utgåvan). Generalstabens Litografiska Anstalts Förlag.
R Core Team. (2025). R: A language and environment for statistical computing [Computer software]. R Foundation for Statistical Computing. https://www.R-project.org/
Wickham H., Hester J., Chang W., Bryan J. (2025). devtools: Tools to Make Developing R Packages Easier. R package version 2.4.6, https://devtools.r-lib.org/.
R package - HultenRangeMaps
Keywords: digitising; digitalisering; habitat; utbredningsområde; species diversity; vascular plant species coverage; historical maps; historiska kartor; vascular plants; kärlväxter; tracheophyta; Range maps; Utbredningskartor; Natural Sciences; Naturvetenskap